Teknik Budidaya Kacang Hijau pada Lahan Kering Beriklim Kering - Kuntyastuti, Henny; Lestari, Sri Ayu Dwi (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
Mungbean is one of the early maturity crops which is resistant to drought. Therefore, this crop is suitable to be cultivated on upland dry climate. Mungbean cultivation technology has been available. However, the improvement of mungbean cultivation is still necessary. The objective of this research was to obtain cultivation technique through combination of plant population, organic and anorganic fertilizers on mungbean to increase the productivity and to provide a residual effect on the successive crop on upland dry climate. This research was conducted on upland Alfisol soil with climate type E in Probolinggo, East Java on dry season 2015 using split plot design, threeplicates. As a main plot was plant spacing, namely: 1) 40 cm x 10 cm, 1 plant/hole, 2) 40 cm x 15 cm, 2 plants/hole, and 3) 40 cm x 20 cm, 2 plants/hole. As a sub plot was combination of organic and anorganic fertilizers, namely: 1) without fertilizer, 2) 50 kg ZA + 50 kg SP-36 + 100 kg KCl/ha, 3) 150 kg Phonska/ha, 4) 5000 kg manure/ha, and 5) 75 kg Phonska + 2500 kg manure/ha. The result showed that the component of mungbean cultivation technology to increase the yield, biomass accumulation, chemical soil fertility and to provide residual effect on upland dry climate with characteristic as Alfisol Probolinggo soil is fertilized with 150 kg Phonska/ha and planted with plant spacing 40 cm x 10 cm, 1 plant/hole or 40 cm x 20 cm, 2 plants/hole. If the priority were biomass production and mungbean protein content, the treatment using 75 kg Phonska + 2500 kg manure/ha could produce biomass 3,19 t/ha (the highest) with K content accumulation of 125,18 kg K/ha (the highest), and N content accumulation in seeds was also the highest at 60,46 kg N/ha.